Development of The Healthcare Model of Thai Traditional Medicine (TTM) for The Older Adults with Hypertension - Varee, Acha; Somsap, Yaowares (Journal of The Royal Thai Army Nurses, 2023)
The purpose of this research was to develop a model of healthcare based on Thai Traditional Medicine for the older adults with hypertension. By utilizing the Participatory Action Research or PAR. Simple random sampling was applied to select 15 participants, based on specific criteria using purposeful sampling. The remaining 36 participants were selected from individuals involved in healthcare in the community. The data were collected via a group discussion, in-depth interviews, participant observations, and field note recordings between July and December 2020. The qualitative data were analyzed by using interpreting, summarizing, and creating a model, whereas the quantitative data were analyzed by using frequency distribution including percentage, mean, and standard deviation. The results are as follows: it was found that after the trial, the mean of health status such as blood pressure, weight, waist circumference, and body mass index was decreasing with statistically significance at P < .05. and the healthcare scores was increasing than before with statistical significance at P < .05. There for, the Healthcare Model of TTM could be a guideline for health care for the older adults with hypertension and also improved the health of individuals, families, and communities.